COVID -19 Vaccine Acceptance among the Residents of Pakistan - Farnaz Ilyas, Saman Hakeem, Nabeela Abbasi, Noor ul Anwar, Shabana Kabeer, Talha Nayab, Maryam Khrushid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Despite the major developments in the vaccination, world health organization due to sudden rise in vaccine-preventable diseases has identified vaccine hesitancy as a major threat. Vaccine hesitancy gets stimulated by the health-related information acquired from various sources, hence is a major problem for health care authorities. Objectives: The main objective of the study was to assess the acceptance of COVID-19 vaccines and its predictors along with the attitude towards these vaccines by the public of Pakistan. Method: This cross-sectional survey was conducted from Jan -March 2022 in Pakistan. The survey from the current study was adopted from a previously conducted research. Male and female participants over the age of 18 were included for the current survey. Participants who declined to participate and providing incomplete details were excluded from the study. Institutional ethical approval for the research was obtained. Chi square test was conducted to assess association between the variable while descriptive statistics were used in form of frequencies. Results: From a total of 1194 participants, there were 232 (19.4%) males and 962 (80.6%) females. When enquired regarding finding vaccines to be safe, 69% of females and 75% of the males both agreed. In response to finding single dose of vaccine better than the multiple dose most of the females (38.5%) and males (47.4%) disagreed. Likewise, majority of females (81%) and males (84.5%) agreed that immunisation will protect against corona virus. In response to pharmaceutical companies being able to develop efficient COVID-19 vaccine, majority of the study participants agreed. When enquired about getting worried on hearing news of side effects, 61% females and 56% males stated not getting worried. Conclusion: An efficient and safe vaccine against COVID-19 is a vital factor in managing and bringing an end to the COVID-19 pandemic, however, wide acceptability of the vaccine is necessary. Public health policy developers must address the wide misinformation spreading regarding the COVID-19 vaccines. Moreover, government should aim to disseminate adequate information about the efficacy and safety of vaccine that will increase the trust of general public on government and will be beneficial in future.